Into the wild: microbiome transplant studies need broader ecological reality. Issue 1921 (26th February 2020) - Greyson-Gaito, Christopher J.; Bartley, Timothy J.; Cottenie, Karl; Jarvis, Will M. C.; Newman, Amy E. M.; Stothart, Mason R.
Abstract : Gut microbial communities (microbiomes) profoundly shape the ecology and evolution of multicellular life. Interactions between host and microbiome appear to be reciprocal, and ecological theory is now being applied to better understand how hosts and their microbiome influence each other. However, some ecological processes that underlie reciprocal host–microbiome interactions may be obscured by the current convention of highly controlled transplantation experiments. Although these approaches have yielded invaluable insights, there is a need for a broader array of approaches to fully understand host–microbiome reciprocity. Using a directed review, we surveyed the breadth of ecological reality in the current literature on gut microbiome transplants with non-human recipients. For 55 studies, we categorized nine key experimental conditions that impact the ecological reality (EcoReality) of the transplant, including host taxon match and donor environment. Using these categories, we rated the EcoReality of each transplant. Encouragingly, the breadth of EcoReality has increased over time, but some components of EcoReality are still relatively unexplored, including recipient host environment and microbiome state. The conceptual framework we develop here maps the landscape of possible EcoReality to highlight where fundamental ecological processes can be considered in future transplant experiments.